Dome control with fuzzy logic - A. Castellón; A. Castellón; G. Larrubia; R. Castillo; A. J. Castro-Tirado; A. J. Castro-Tirado; E. Fernández-García; C. Pérez del Pulgar; A. Reina; S. Castillo-Carrión (Frontiers in Astronomy and Space Sciences, 2022)
This article describes a fuzzy logic-based method optimized for the dome control of a robotic astronomical observatory. A Mamdani inference has been developed in order to make the decision to open or close the dome. The input variables are obtained from data received from a weather station besides the percentage of cloudy sky as derived by two allsky cameras. The software has been tested at the BOOTES-1 observatory as part of the BOOTES Global Network of Robotic Telescopes led by IAA-CSIC.